2015
DOI: 10.1186/s11689-015-9106-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for feature conjunctions: an fMRI study comparing alcohol-related neurodevelopmental disorder (ARND) to ADHD

Abstract: BackgroundAlcohol-related neurodevelopmental disorder (ARND) falls under the umbrella of fetal alcohol spectrum disorder (FASD). Diagnosis of ARND is difficult because individuals do not demonstrate the characteristic facial features associated with fetal alcohol syndrome (FAS). While attentional problems in ARND are similar to those found in attention-deficit/hyperactivity disorder (ADHD), the underlying impairment in attention pathways may be different.MethodsFunctional magnetic resonance imaging (fMRI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
(77 reference statements)
4
22
0
Order By: Relevance
“…They may, in turn, have necessitated increased recruitment of visual processing regions to complete the task. Other studies also support the possibility that SWM deficits in FASD may be secondary to visual processing, which is consistent with alterations in the bottom-up processing in children with ARND suggested by O’Conaill et al (2015). For example, a study by Malisza et al (2012) found decreased occipital activation during a 0-back task in children with ARND relative to controls, indicating inefficient visual processing pathways or compromised visual attention in the ARND group.…”
Section: Discussionsupporting
confidence: 60%
“…They may, in turn, have necessitated increased recruitment of visual processing regions to complete the task. Other studies also support the possibility that SWM deficits in FASD may be secondary to visual processing, which is consistent with alterations in the bottom-up processing in children with ARND suggested by O’Conaill et al (2015). For example, a study by Malisza et al (2012) found decreased occipital activation during a 0-back task in children with ARND relative to controls, indicating inefficient visual processing pathways or compromised visual attention in the ARND group.…”
Section: Discussionsupporting
confidence: 60%
“…distractors whose color and shape were identical and different from the target's), adolescents with ARDN had much more extensive activations in the dorsal frontoparietal network, which included the attention pathways, compared to the controls. Yet, when the search task became more complicated with the distractors either having the same color or shape as the target's, subjects with ARND showed only a small change in activation from the simpler task, while healthy subjects exhibited a substantial increase in cortical activation in the frontal, parietal, temporal and lateral occipital regions [76].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…18 appeared alone then in an array [76]. In a simple search task where the target character reappeared together with three other characters (i.e.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations